IKTIOFAUNA DI DANAU SEMAYANG-MELINTANG KAWASAN MAHAKAM TENGAH, KALIMANTAN TIMUR [Ichthyofauna of Semayang-Melintang Lakes Central Mahakam Area, East Kalimantan] - Haryono Haryono (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2006)
Kota Bangun is production center of fisheries in East Kalimantan. This area has waters, i.e. Mahakam River, lakes of Semayang, Melintang and Jempang. Study of freshwater fishes in Semayang and Melintang lakes was done during September and October 1995 (dry season). The aims of study were to determine fish diversity, structure, composition, potency, abundance, distribution and habitat condition. The result recorded 15 species. Barbodes collingwoodi have dominant of abundance and distribution; and Cyprinidae was dominant family. Both the Semayang and Melintang lakes have high of similarity index and evenness index. The diversity index in Melintang was higher than Semayang.